2021
DOI: 10.1186/s13244-021-01086-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive ability of CT findings in the differentiation of complicated and uncomplicated appendicitis: a retrospective investigation of 201 patients undergone appendectomy at initial admission

Abstract: Background Paradigm shift toward nonoperative management (NOM) of adult appendicitis has made computed tomography (CT) more important than ever, particularly in differentiating complicated from uncomplicated disease. Complete surgical and pathological data of appendicitis in a place where appendectomy at initial admission is a standard of care would allow retrospective review of preoperative CT for performance and predictive ability in identifying those that may benefit from NOM in the future. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
9
1
1
Order By: Relevance
“…23 As phlegmonous and gangrenous appendicitis seem to be separate entities, one of which may resolve spontaneously and another that progresses to gangrene and perforation, diagnostic improvements in CT and the application of artificial intelligence and advanced combinatorial tools for distinguishing these two entities, especially in middle-income countries, helped in choosing treatment and reduced the perforation rate and adverse events. [24][25][26][27] Surgical advances have begun to reduce complications, and the promoted laparoscopic appendectomy is reported to be associated with a lower incidence of wound infection and post-intervention morbidity, shorter hospital stay, and better quality of life scores than open appendectomy. [28][29][30] In addition, endoscopic retrograde appendicitis therapy, which is a new and minimally invasive technique, has emerged as a promising non-invasive treatment for acute uncomplicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…23 As phlegmonous and gangrenous appendicitis seem to be separate entities, one of which may resolve spontaneously and another that progresses to gangrene and perforation, diagnostic improvements in CT and the application of artificial intelligence and advanced combinatorial tools for distinguishing these two entities, especially in middle-income countries, helped in choosing treatment and reduced the perforation rate and adverse events. [24][25][26][27] Surgical advances have begun to reduce complications, and the promoted laparoscopic appendectomy is reported to be associated with a lower incidence of wound infection and post-intervention morbidity, shorter hospital stay, and better quality of life scores than open appendectomy. [28][29][30] In addition, endoscopic retrograde appendicitis therapy, which is a new and minimally invasive technique, has emerged as a promising non-invasive treatment for acute uncomplicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being commonly used for its differential diagnosis, CT imaging findings are generally non-specific and limited, although there are various characteristics of imaging reported to be associated with complicated appendicitis in the literature (11). In previous studies, CT was reported to have an overall sensitivity of 64%-88% and specificity of 75%-99% in differentiating between complicated and uncomplicated appendicitis (22)(23)(24)(25)(26)(27). In the present study, CT had a sensitivity of 83.3% and a specificity of 79.2% in differentiating between complicated and uncomplicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis by Kim et al, the relatively increasing appendiceal contrast-enhancement had a pooled sensitivity of 74.94% and a pooled specificity of 9.25% (11). Mahankali et al used MHE in their CT-based severity assessment of acute appendicitis, while Iamwat et al used MHE as one of the criteria for differentiating between complicated and uncomplicated appendicitis (15,27). In the present study, MHE was another finding that was more common in complicated appendicitis (65.3%).…”
Section: Discussionmentioning
confidence: 99%
“…However, distinguishing between simple and complicated appendicitis in the absence of surgery is a hot topic in current clinical research. By statistical analysis of preoperative computerised tomography (CT) scans [ 7 ] of acute appendicitis [ 8 ], the volume and distribution of platelets in the blood have been reported. The levels of bilirubin [ 9 ], serum sodium [ 10 ] and 5-hydroxyindoleacetic acid [ 11 ] and the neutrophil to lymphocyte ratio [ 12 , 13 ] have been used to distinguish between simple and complicated appendicitis.…”
Section: Methodsmentioning
confidence: 99%